2010
DOI: 10.1159/000276566
|View full text |Cite
|
Sign up to set email alerts
|

Time-course Effects of Increased Fatty Acid Supply on the Expression of Genes Involved in Lipid/Glucose Metabolism in Muscle Cells

Abstract: Fatty acid (FA) oversupply in skeletal muscle is related with metabolic disorders associated to obesity, and also with normal physiological responses. We studied, in vivo and in vitro, the chronological response to physiological increases of FA, analyzing the expression of selected genes important for glucose/lipid metabolism. An in vivo sequential model of fasting (known to increase circulating FA) and refeeding was used in male Wistar rats to study soleus (more oxidative) and gastrocnemius (more glycolytic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
4
22
1
Order By: Relevance
“…Regarding this, two important questions must be outlined: 1) due to the key functions of PGC1α, this effect may be directly related to other transcriptional changes observed in this work and the rapid response may suggest that PGC1α may be a key molecule orchestrating ulterior effects of leptin in the cells, and 2) how can the expression of PGC1α when leptin acts on muscle cells be increased. With respect to the first question, this is not the first time we have observed a rapid transient increase of PGC1α expression which may be related with posterior transcriptional changes facing a metabolic challenge; we have reported that sequential fasting in rat muscle in vivo and FFA (oleic/linoleic) or adrenaline treatment of C2C12 cells cause a peak of increased PGC1α mRNA levels after 4h (fasting) or 3h (FFA or adrenaline), thereafter returning to basal levels in all cases [7,8]. To address the second question, it is important to note that in muscle cells leptin is able to activate the catalytic α2 subunit of AMPK promoting its kinase activity on downstream molecules [5].…”
Section: Nozhenko/rodríguez/palou: Leptin and Metabolic Pattern In Mumentioning
confidence: 78%
See 2 more Smart Citations
“…Regarding this, two important questions must be outlined: 1) due to the key functions of PGC1α, this effect may be directly related to other transcriptional changes observed in this work and the rapid response may suggest that PGC1α may be a key molecule orchestrating ulterior effects of leptin in the cells, and 2) how can the expression of PGC1α when leptin acts on muscle cells be increased. With respect to the first question, this is not the first time we have observed a rapid transient increase of PGC1α expression which may be related with posterior transcriptional changes facing a metabolic challenge; we have reported that sequential fasting in rat muscle in vivo and FFA (oleic/linoleic) or adrenaline treatment of C2C12 cells cause a peak of increased PGC1α mRNA levels after 4h (fasting) or 3h (FFA or adrenaline), thereafter returning to basal levels in all cases [7,8]. To address the second question, it is important to note that in muscle cells leptin is able to activate the catalytic α2 subunit of AMPK promoting its kinase activity on downstream molecules [5].…”
Section: Nozhenko/rodríguez/palou: Leptin and Metabolic Pattern In Mumentioning
confidence: 78%
“…We performed a time-sequential and dose-dependent model (similar to previous works [7,8]) of differentiated cultured muscle cells (C2C12) treated with leptin to characterize its effects on the expression of the strategic molecules described above. We describe here that leptin causes a rapid response of myocytes by inducing the expression of key genes involved in metabolic and fuel control (especially those codifying PGC1α, mCPT1, UCP3 and PDK4) and of the myokine IL6.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies may be partly due to differences in the fatty acid compositions of the diets, since it has been shown that, depending on their chain length and saturation level, fatty acids have greatly varying effects on PGC-1α expression [52]. PGC-1α mRNA and protein expression peak rapidly after a stimulus, such as an exercise bout [14,26,29] or an increase in the concentration of serum fatty acids [53]. After a period of adaptation, no change or only slight changes in PGC-1α mRNA and protein levels have been observed, after 4 weeks of high-fat diet [11] or, as in the present study, after a high-fat diet and/or exercise for 19 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…SFR mitochondria exhibited increased ROS generation despite simultaneously overexpressing UCP2. Although the function of UCP2 is still unclear, it has been linked to the accumulation of FFAs in hepatocytes and muscle cells (12,46) and to mitochondrial ROS production (43). The mild uncoupling mediated by UCP2 may accelerate respiration rates and reduce the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%